THE ANALYSIS OF FACTORS AFFECTING DIVIDEND PAYOUT RATIO IN THE GO PUBLIC COMPANIES LISTED AT INDONESIA STOCK EXCHANGE IN PERIOD 2006-2010 - Alfon’s, Jeffry Ray (Jurnal Ilmiah Mahasiswa FEB, 2012)
Research is conducted to examine the effect of variable  Cash Ratio  (CR), Growth,   Return on Asset (ROA) and Net Profit Margin (NPM) on Dividend Payout Ratio  in the company listed at Indonesia Stock Exchange (IDX) during 2006-2010. Sampling technique is  purposive sampling. The criteria  involve: (1)  The company listed during 2006-2010, (2) The company publish financial statements during 2006-2010 Data are collected from the publication of Indonesian Capital Market Directory (ICMD, 2011) and from these data, the sample is obtained, which is  374 companies of the population of 450 companies listed at ISE. The analysis technique is multiple regression with smallest square equation. Statistical-test will examine the simultaneous effect significance at   5 %  level of significance. Classical assumption test involves normality test, multicolinearity test, heteroscedasticity test, and autocorrelation test.  Result of analysis indicates that variables of  Return on Asset  (ROA) are partially significant against DPR. Meanwhile, variables of Growth Net Profit Margin and  Debt To Total Assets (DTA)  do not  have an effect on DPR. Simultaneously, Growth, Return on Asset (ROA), Net Profit Margin (NPM), and Debt To Total Assets (DTA)  are influencing DPR. The predictive ability of four variables on DPR is 7,5 %, while the remaining  92,5 % are affected by other factors excluded from research model.  Keywords: Growth, Return on Asset  (ROA), Net Profit Margin  (NPM), Debt To Total Assets (DTA),  and Dividend Payout Ratio (DPR)